Simulation studies on shape and growth kinetics for fractal aggregates in aerosol and colloidal systems - Heinson, William Raymond (Kansas State University, 2015)
The aim of this work is to explore, using computational techniques that simulate the motion and subsequent aggregation of particles in aerosol and colloidal systems, many common but not well studied systems that form fractal clusters. Primarily the focus is on cluster shape and growth kinetics. The structure of clusters made under diffusion limited cluster-cluster aggregation (DLCA) is looked at. More specifically, the shape anisotropy is found to have an inverse relationship on the scaling prefactor "k"_"0" and have no effect on the fractal dimension "D"_"f". An analytical model that predicts the shape and fractal dimension of diffusion limited cluster-cluster aggregates is tested and successfully predicts cluster shape and dimensionality. Growth kinetics of cluster-cluster aggregation in the free molecular regime where the system starts with ballistic motion and then transitions to diffusive motion as the aggregates grow in size is studied. It is shown that the kinetic exponent will crossover from the ballistic to the diffusional values and the onset of this crossover is predicted by when the nearest neighbor Knudsen number reaches unity. Simulations were carried out for a system in which molten particles coalesce into spheres, then cool till coalescing stops and finally the polydispersed monomers stick at point contacts to form fractal clusters. The kinetic exponent and overall cluster structure for these aggregates was found to be in agreement with DLCA that started with monodispersed monomers. Colloidal aggregation in the presence of shear was studied in detail. Study of a colloidal system characterized a by short-range attractive potential showed that weak shear enhanced the aggregation process. Strong shear led to fragmentation and subsequent nucleation as cluster growth rebounded after an induction time.
Keywords: DLCA; Aggregation; Fractal; Physics (0605)